FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN STRESS KERJA PADA PETUGAS CALL CENTER NOMOR TUNGGAL PANGGILAN DARURAT (NTPD) JAKARTA SIAGA 112 DI BADAN PENANGGULANGAN BENCANA DAERAH DKI JAKARTA TAHUN 2021 - Kevin Antonio Situmeang; Ade Heryana; Intan Silviana Mustikawati; Anggun Nabila (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Employees work stress can harm themselves and the company. The purpose of this study was to determine the factors associated with work stress on the call center officer of the Jakarta Emergency Call 112 (NTPD). Research design used cross sectional with quantitative approach. The study was conducted in April 2021 - August 2021. Sample were 40 participant that selected with total sampling method. Data was analyze in univariate and bivariate tests using the chi-square statistical test with α = 0.05. The results showed call center officers with female sex 21 people (52.5%), College 33 people (82.5%), no work stress 23 people (54,7%), moderate workload 21 people (52.5 %), positive work climate 24 people (60.0%). Based on bivariate analysis, it was found that there was a relationship between work stress of call center officers and education (p value = 0.029, PR = 2.571). Based on bivariate analysis, it was found that there was a relationship between work stress of call center officers and education (p value = 0.029, PR = 2.571). It is hoped that the company's management will conduct emergency training and communication training on a regular basis to help officers with low education be better prepared to serve the community. In addition, management provides stress management counseling activities and provides sports facilities and vacation activities for staff relaxation.